Effect of the of 10-valent pneumococcal conjugate vaccine in Nepal 4 years after introduction: an observational cohort study - Shrestha, S; Gurung, M; Amatya, P; Bijukchhe, S; Bose, AS; Carter, MJ; Gautam, MC; Gurung, S; Hinds, J; Kandasamy, R; Kelly, S; Khadka, B; et al. (Elsevierhttps://www.thelancet.com/journals/langlo/home, 2022)
Background In Nepal, Streptococcus pneumoniae (pneumococcus) is a common cause of bacterial pneumonia in children, and is a major health concern. There are few data on the effect of vaccination on the disease or colonisation with pneumococci in the nasopharynx of children in this setting. The 10-valent pneumococcal conjugate vaccine (PCV10) was introduced into the routine infant immunisation schedule in Nepal in 2015. We aimed to investigate the effect of the introduction of PCV10 on pneumococcal carriage and disease in children in Nepal.